Earth Science Education 4. Geoliteracy Canada, A National Geoscience Education Initiative - Clague, John; Turner, Robert; Bates, Jennifer; Haidl, Fran; Morgan, Alan; Vodden, Christy (Geoscience Canada, 2001)
Summary Harth scientists are collectively responsible for ensuring that geoscience knowledge is incorporated into decisions about land use in Canada. The future of our discipline depends to a considerable extent on an educated public that tealizes the value of earth science information. The vitality of earth sciences also depends on our ability to convince bright students to enter our profession. In this paper, we propose an initiative in geoscience education, Geo-literacy Canada, based on expanded delivery of, and better linkages among, four national programs and an upcoming international conference. The programs that underpin this initiative are EdGEO, EarthNet, WAT ON EARTH, and Geoscape Canada. These national programs are linked, in turn, to the many local and regional geoscience education enterprises across the country. The Canadian Geo-science Education Network, the education committee of the Canadian Geoscience Council (CGC), will provide national co-ordination of the initiative.